UJI AKTIVITAS ANTIBAKTERI EKSTRAK DAUN TEH-TEHAN (Acalypha siamensis) TERHADAP BAKTERI Staphylococcus aureus DENGAN MENGGUNAKAN METODE CAKRAM DI PROGRAM STUDI S1 FARMASI UNIVERSITAS IMELDA MEDAN - Maya Syari, Dina; Aprilla, Chindy (Universitas Imelda Medan, 2022)
Teh-tehan (Acalypha siamensis) is a plant that has many branches into the bush with a height of 1-2 m.Staphylococcus aureus is a bacterium found on the skin and can be pathogenic, this bacterium can cause ringworm, pus, boils and others. The purpose of this study was to determine the antibacterial activity of the ethanol extract of tea-tehan (Acalypha siamensis) leaves against Staphylococcus aureus using the disc method. This research is descriptive qualitative with a comparison of the extract concentration of 20%, 30%, 50%, and 80% with a positive control of cefadroxile and a negative control of aquadest. The test results showed that the ethanol extract of Teh-tehan leaves had antibacterial activity against Staphylococcus aureus which was indicated by the presence of an inhibition zone. Staphylococcus aureus bacteria gave the highest inhibition zone at a concentration of 80% with an inhibition zone diameter of 12.10 mm, while the Cefadroxil control was 30.7 mm. Based on the one way ANOVA data analysis test that there is a significant difference in the antibacterial inhibition of each concentration of tea-tea leaf extract.